Effect of Concept Maps on Knowledge Retention in Dental Students (Medical Forum Monthly, 2024)
Objective: To determine the effect of Concept Maps on Knowledge Retention in Dental students.Study Design: Randomized study.Place and Duration of Study: This study was conducted at the Jinnah Medical and Dental College, Karachi.Materials and Methods: A randomized controlled trial was conducted on fifty students of BDS first year at the Jinnah Medical and Dental College, Karachi. The students were randomly divided into two groups. Initially the whole class was taught thefirst unit of Biochemistry (Carbohydrates) by the conventional method. It was followed by a Multiple Choice Questions test which established the equivalence in the mean scores of the two groups. The Intervention group now attended a workshop on “Concept Maps”. In the next two units (Proteins and Lipids), the Intervention group made Concept Maps while the Control group continued with the conventional method. Each unit ended with an MCQ test. The score of the Unit test was taken as an indicator of short term retention of knowledge. Two months later, an unscheduled Retest was given consisting of all the MCQ given in the three Unit tests. The difference between the scores of the Unit tests and Retest was taken as an indicator of long term retention of knowledge. The mean scores of the two groups were compared using Independent samples t-test.Result: No significant difference was found in the mean scores of the Intervention and Control groups in the Unit tests. But in the Retest the Intervention group performed significantly better (p ‹ 0.01) than the Control group.Conclusion: Learning through Concept Maps improves long term retention of knowledge.